Armed Banditry and Statehood Challenges in North-Western Nigeria - Abdullahi , Idris Ibrahim (Kashere Journal of Politics and International Relations, 2024)
This paper attempts to examine Armed Banditry and Statehood Challenges in North-Western Nigeria as part of the threats to national security that has setback the nation building. Therefore, states of Zamfara, Katsina, Kaduna, Sokoto and Kebbi in the zone are facing the ever increasing and unquantifiable monstrosities of armed banditry that resulted to many villages deserted, thousands of innocent people killed, thousands kidnapped for ransom and hundreds thousands fled their homes. The study employed qualitative research method through the use of secondary sources of data for proper analysis. To this effect, the paper adopts Weber Conceptual Clarification of state which noted that state is a compulsory political organization with a centralized government that maintains a monopoly of the legitimate use of force within a certain territory. The paper finds out that, in North-Western Nigeria armed bandits have created a semblance of parallel authority that denies bonafide citizens access to their ancestral farmlands, imposing levies on communities, usurped power and have now begun to appoint District Heads and forests across the zone were grossly unregulated turned into their operational base. The paper recommends among others, powerful centralized government that maintains a monopoly of the legitimate use of force, effective control of ungoverned spaces and protection racket in the vein of organized crime that would provide effective preventive measure, management strategies for intelligence gathering so that security agencies could be proactive and reasonably predict potential security threats with near perfect accuracy rather than being reactive.